Temu Kembali Informasi Lintas Bahasa untuk Dokumen Berita Berbahasa Indonesia-Inggris Menggunakan Metode BM25 - Putri Rahma Iriani; Indriati Indriati; Putra Pandu Adikara (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
News is an information about someone's needs to find out what is happening. Efforts to get relevant news from a variety of languages ​​and documents are not easy to obtain. News documents usually written in foreign language. This becomes difficult because not all users understand foreign language, while the news needed in the collection of foreign language. Users can read one by one to get news as it needed, but this process is inefficient and will take a long time. A cross-language automatic news search system is needed to solve this problem, where users only enter requests with the native language and the system will recover documents in other languages. This problem can solve by creating a system to obtain automatic news without language barriers. This system will builds using the BM25 method which has been proven to be able to improve documents that are relevant to the ranking. The free parameters used are k1 = 2.5 and b = 8.0. Weighting is done by comparing IDF BM25 and IDF modification which results in the highest value of 0.95 with k = 5 in testing of precision@k.